Biochar as a cheap and environmental friendly filler able to improve polymer mechanical properties. (January 2019) - Giorcelli, Mauro; Khan, Aamer; Pugno, Nicola M.; Rosso, Carlo; Tagliaferro, Alberto
Abstract: This study reports about the use of Biochar derived from maple tree as a filler in Epoxy resin. Maple tree blocks were pyrolyzed in inert atmosphere at 600 °C and 1000 °C respectively and were characterized morphologically. The composite mechanical properties, i.e. stress-strain curves and related parameters (ultimate tensile strength, Young modulus, resilience, tensile toughness) were recorded as well as their friction coefficient. It is shown that at very low wt.% of the filler, the Young modulus is increased while at higher wt.% (2 wt% and above) the fragile behavior of the resin was converted in a ductile one, as elongation at break increased from 0.02 to 0.12. A huge impact of the filler is observed on tensile toughness as for the best sample is increased 11 times with respect with pure resin. A simple model able to describe the results and make predictions on other wt.% is presented as well. Highlights: Morphological characterization for Biochars and composites. Full mechanical composite characterization. Mathematical model.